2018
DOI: 10.1002/biot.201800050
|View full text |Cite
|
Sign up to set email alerts
|

Low Protease Content in Medicago truncatula Cell Cultures Facilitates Recombinant Protein Production

Abstract: Medicago truncatula is an established model for studying legume biology. More recently, it has also been exploited as a Molecular Farming platform for the production of recombinant proteins, with the successful expression of fungal and human proteins in plants and cell suspension cultures of this species. One of the challenges that now must be overcome is the degradation of final products during production and downstream processing stages. In the M. truncatula genome, there are more than 400 putative protease-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Consequently, searching for plant species with low proteolytic activity will provide improved recombinant protein stability and the screening of plant species with low protease activity is, therefore, urgently required. In fact, Santos et al [154] showed that the number of proteases found in Medicago was considerably lower. Genomic and proteomic approaches will allow us to advance in the knowledge of the specific role of the different proteases and their inhibitors and this will result in the development of new strategies to improve plant-based recombinant protein production significantly.…”
Section: Challenges and Perspectives In Preventing Proteolysis In mentioning
confidence: 99%
“…Consequently, searching for plant species with low proteolytic activity will provide improved recombinant protein stability and the screening of plant species with low protease activity is, therefore, urgently required. In fact, Santos et al [154] showed that the number of proteases found in Medicago was considerably lower. Genomic and proteomic approaches will allow us to advance in the knowledge of the specific role of the different proteases and their inhibitors and this will result in the development of new strategies to improve plant-based recombinant protein production significantly.…”
Section: Challenges and Perspectives In Preventing Proteolysis In mentioning
confidence: 99%
“…Although its role is still unknown, the fact that the granulin-domains were uncovered may help explain a possible interaction between the cysteine proteases and cardosin B. In human cells, progranulin has been found to interact with both prosaposin 29 , a glycoprotein involved in the lysosomal trafficking pathway, and cathepsin D, a human aspartic protease 32,33 ). Like most typical plant APs, cardosin B contains a saposin-like domain corresponding to the PSI segment.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the same or closely related proteases account for bNAb processing in different plants irrespective of the type of tissue or cell line. Although the plant proteases responsible for cleavage within the CDR H3 loops of bNAbs have not yet been identified, previous inhibitor studies have indicated that serine and cysteine proteases could be involved in these processing reactions …”
Section: Discussionmentioning
confidence: 99%